End of the Supercycle and Growth of Commodity Producers : The Case of Chile - Eyraud, Luc. (Washington, D.C. : International Monetary Fund, 2015)
This paper estimates the effect of copper prices on Chile's growth at various time horizons. We find that a price decline is likely to have a durable (although not permanent) effect on GDP growth: while the impact is the strongest in the first 3 years after the shock, the transition towards the new lower steady-state GDP level generally takes 5-10 years. From a production function perspective, the GDP growth slowdown is mainly driven by lower capital accumulation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Chile